2019
DOI: 10.3390/molecules24203799
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Organic Acids, Amino Acids and Phenolic Compounds on Antioxidant Characteristic of Zhenjiang Aromatic Vinegar

Abstract: Zhenjiang aromatic vinegar (ZAV) is one of the famous Chinese vinegars, which contains various physicochemical and bioactive compositions. In the present study, physicochemical properties and total antioxidant activity were detected in ZAV samples. The correlation between of organic acids, amino acids, phenolic compounds, and the antioxidant activity of ZAV were explored. The results showed that contents of total acids, soluble solids, reducing sugar and total antioxidant activity in ZAV were increased with ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 41 publications
4
46
0
Order By: Relevance
“…The primary metabolites comprising carbohydrates (sucrose and fructose) and organic acids (citric acid, succinic acid, fumaric acid, and aconitic acid) were also shown to be correlated with the antioxidant and wound healing activities. These findings are in accordance with other studies that reported primary metabolites, such as organic acids and carbohydrates, also contribute to antioxidant and wound healing activities of a plant extract [59,60].…”
Section: Correlation Between Identified Metabolites and Antioxidant Asupporting
confidence: 93%
See 1 more Smart Citation
“…The primary metabolites comprising carbohydrates (sucrose and fructose) and organic acids (citric acid, succinic acid, fumaric acid, and aconitic acid) were also shown to be correlated with the antioxidant and wound healing activities. These findings are in accordance with other studies that reported primary metabolites, such as organic acids and carbohydrates, also contribute to antioxidant and wound healing activities of a plant extract [59,60].…”
Section: Correlation Between Identified Metabolites and Antioxidant Asupporting
confidence: 93%
“…The antioxidant activities expressed by flavonoids could be related to their structure-antioxidant activity relationships. The presence of one or more phenolic hydroxyl groups (-OH) in their structure plays a significant role in these activities [59,[64][65][66]. The contribution of flavonoids, especially catechin, luteolin, and apigenin derivatives, in antioxidant action can be explained by direct scavenging of ROS via hydrogen atom donation, which is one of the common antioxidant action mechanisms of flavonoids [67].…”
Section: Discussionmentioning
confidence: 99%
“…The elongation of the droplet indicates the oxidation of the liquid metal as the oxide layer significantly lowered its surface tension. 15,[43][44][45][46] Locomotion of the droplet was restored after we change the polarity of the potential to electrochemically reduce the liquid metal ( Figure 3C). This experiment clearly demonstrates that the motion of EGaIn droplets can be flexibly controlled by altering the property of their surface (also see Movie S5).…”
Section: Resultsmentioning
confidence: 99%
“…The effective components in it are relatively abundant and stable through the fingerprint analysis and amino acid analysis. During the brewing process, aromatic vinegar produces many bioactive compounds, such as organic acids, amino acids and phenolic compounds, which play important roles in antioxidant activities (Zhang et al, 2019). In addition, polyphenols, flavonoids, and melanoidins were found in Hengshun aromatic vinegar, which play crucial roles in diseases prevention and contribute benefits to human health (Zhao et al, 2018;Duan et al, 2019).…”
Section: Discussionmentioning
confidence: 99%